Gravity modelling of ice thickness and valley geometry on Taku Glacier (T'aak̲ú K̲wáan Sít'i), Alaska - Louise Borthwick; Atsuhiro Muto; Kirsty Tinto (Journal of Glaciology)
Taku Glacier recently began retreating for the first time since the late 19th century but limited observations of its bed leaves uncertainties on how this retreat will proceed. In this study, we use ground-based gravity measurements to improve the extent of bed-elevation estimates on the Taku by modelling the glacier in 3D. We find the across-flow geometry of the middle to upper reach of the Taku and the Matthes branch has a step-like feature near the edge and a wide, flat bottom. We constrain the ice thickness along flow within uncertainty limits and provide a range of expected values. Along the centre line of our model, we find a maximum ice thickness of 1556 ± 143 m and the deepest bed at 445 ± 166 m below sea level. The along-flow results also delineate two bedrock bumps, which could help stabilise the retreat of the Taku when its terminus is submerged in water. We model the bed to be below sea level until at least 35 km upstream of the terminus where the Matthes branch joins the main branch, improving constraints on how far upstream the Taku would be vulnerable to marine retreat.